2020
DOI: 10.31234/osf.io/5rj6y
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sequence alignment of folk song melodies reveals cross-cultural regularities of musical evolution

Abstract: Melodies are culturally transmitted sequences of notes that evolve through time in a manner that broadly parallels the process of molecular sequence evolution. While gene sequencing and the identification of general mechanisms of DNA transmission and mutation have revolutionized our understanding of biological evolution, the nature - and even the existence - of cross-culturally universal mechanisms of musical evolution remains debated. Here we adapt sequence alignment algorithms from molecular genetics to anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…For example, some types of melodic modi cations may be more likely than others because they are easier to sing or less noticeable to listeners. In a recent study of over 10,000 Japanese and English folk melodies, Savage et al (2020) found that modi cations that have a smaller impact on the melody are more likely to change and have those changes persist in the population. This nding was consistent despite striking di erences in the scales used in Japanese and English folk music.…”
Section: Traditional and Folk Musicmentioning
confidence: 99%
“…For example, some types of melodic modi cations may be more likely than others because they are easier to sing or less noticeable to listeners. In a recent study of over 10,000 Japanese and English folk melodies, Savage et al (2020) found that modi cations that have a smaller impact on the melody are more likely to change and have those changes persist in the population. This nding was consistent despite striking di erences in the scales used in Japanese and English folk music.…”
Section: Traditional and Folk Musicmentioning
confidence: 99%
“…Naively, one might expect that oral transmission just introduces random noise into the sung production. In practice, however, it is thought that oral transmission shapes musical systems in systematic ways that reflect human reproduction biases (Mehr, Krasnow, Bryant, & Hagen, 2020; Savage et al, 2022). With cultural exposure, people internalize these regularities and, in turn, are more likely to feature them in future productions.…”
Section: Introductionmentioning
confidence: 99%
“…The optimal balance between familiarity and innovation in artistic domains will depend, further, on distinct features of specific artistic genres and social contexts. While improvisation is important in, for example, jazz and North Indian classical music, folk music is by nature relatively conservative, with individual innovation limited by an emphasis on preserving traditional tunes (Vallely, 2011) and by the constraints of typical folk tune structure, phrasing and tonality (Savage, Chiba, Currie, Suzuki, & Atkinson, 2020). The finding that session tunes of intermediate complexity are most popular is consistent with previous evidence that preferences for novelty in music trade off against preferences for predictability (Chmiel & Schubert, 2017;Delplanque et al, 2019;North & Hargreaves, 1995;Van Geert & Wagemans, 2020), confirming the suggestion of folk scholars that tunes with an optimal balance of playability and aesthetic interest are most likely to become established favourites (Hillhouse, 2013;Vallely, 2011).…”
Section: Discussionmentioning
confidence: 99%